Meat quality in European quail supplemented with sources of polyunsaturated fatty acids - Leite Cavalcante, Cecylyana (Revista Ciência Agronômica, 2021)
The aim of this study was to carry out a comparative evaluation of the effect of adding different sources of PUFAS to the diet on performance, carcass yield, chemical composition, and the physical characteristics of breast meat from European quail. A tot al of 280 European quail with a mean weight of 90.97 ± 0.5 g, during the growth period and ranging from 14 to 42 days of age, were distributed in a completely randomised design with seven treatments, and fi ve replications of eight birds each. The quail were fed on diets containing 2% of the following lipid sources and mixtures: 1. Soybean oil (SBO); 2. Linseed oil (LSO); 3. Brazil Nut Oil (BNO); 4. Fish oil (FSO); 5. LSO+SBO; 6. BNO+SBO; and 7. FSO+SBO. Performance measures, such as carcass yield and meat quality (chemical composition, pH, centrifugation loss, weight loss by cooking, shear strength and colour) were evaluated. The performance measures (weight gain, feed intake and feed conversion) were infl uenced by the source of lipids. The FSO diet showed better performance. Quails fed on the BNO (18.27 g/bird/day) and LSO (17.58 g/bird/day) diets had a higher feed intake. Carcass yield and the chemical composition of the meat showed no signifi cant differences (P > 0.05), while the chemical and physical characteristics showed differences between the lipid sources added to the diet. The addition of sources of polyunsaturated fatty acids caused no harmful effects to the birds or undesirable changes in meat quality.